PERSONALITY TRAITS OF THE MAIN CHARACTER AND THEIR DESCRIPTION IN “THE NIGHTMARE BEFORE CHRISTMAS” - Jayantini, I Gusti Agung Sri Rwa; Umbas, Ronald; Ronsmin, Felisita; Hading, Yuliana Resti; Tentang, Fotina (Lire Journal (Journal of Linguistics and Literature), 2024)
Short stories provide readers series of events that take place in the life of the characters. For both enjoyment and reflection, the events are considerably constructed by the writer to share meaningful values. Readers can learn how the characters solve problems to overcome obstacles. This study discusses the personality traits of the main character and how they are described in the short story “The Nightmare before Christmas.” Qualitative method, with the approach of content analysis focusing on the main character Jack Skellington, was applied. Through a close reading, it was found that the main character was a brave person who loved to experience new things. For his brevity to a new breakthrough in what he had done in the past, he was kind of cool person. Fundamentally, he was also a loving and loyal character. All of these inner strengths contribute to make the character more likeable. Meanwhile, the personality of the main character is predominantly shown through mixing method, that is a mixed of dramatic, characters on characters, and contextual characterization. This indicates that the main character, Jack Skellington is delineated by giving indirect descriptions and implicit statements aiming to show the personality traits of the main character to the readers